Abstract ID: 38 Investigating energy deposition in cellular targets using multiscale tissue models. (October 2017) - Oliver, Patricia; Thomson, Rowan M.
Abstract : Purpose: To investigate energy deposition in subcellular targets, quantify the microdosimetric spread in a population of cells, and determine how these results depend on details of multiscale Monte Carlo tissue models. Methods: Multiscale tissue models are developed involving microscopically-detailed regions of interest (ROIs) embedded in bulk tissue phantoms irradiated by photons (20 keV to 1.25 MeV). Each ROI includes >1500 explicitly-modelled cells; specific energy (energy imparted per unit mass) is scored in nuclei and cytoplasm compartments using the EGSnrc user-code egs_chamber. Different cell arrangement methods and cell/nucleus size distributions are investigated. These microscopic tissue structure models are developed using published data on cell elemental compositions, sizes and number densities. Five cancerous/normal human soft tissues and water are considered. Use of egs_chamber at low doses (∼mGy), considering subcellular (∼micron) targets, is validated by comparison with results from the published literature. Results: Populations of 1000 cells generate (normalized) specific energy distributions f ( z ) indistinguishable from those of a larger population, which suggests that 1000 is an adequate population size for statistical analysis. Validation test results are in good agreement with published experimental and computational data. For ∼mGy doses, there is considerable variation in energy deposition (microdosimetric spread) throughout a cell population: considering muscle with 7.5 microns (3 microns) cell (nucleus) radius and a dose of 4 mGy, the standard deviation of specific energy (relative to the mean) for nuclear targets is 177% for 50 keV photons, and 114% for a Cobalt-60 spectrum. If the nuclear radius increases to 6 microns, then the relative standard deviation decreases to 74% and 47% for 50 keV and Cobalt-60, respectively. The mean specific energy for nuclei differs from bulk tissue dose by up to 30%, depending on cellular elemental compositions. Conclusions: At low doses, there is considerable variation in energy deposition within a population of cells. Mean nucleus specific energy generally differs from corresponding bulk tissue dose. Results highlight the importance of model validation and microdosimetric considerations at low doses, and indicate that energy deposition within subcellular targets is sensitive to cell morphology and composition, phantom medium, source energy, and dose.